COMPARING THE EFFECTIVENESS OF LED TV/LCD AND WHITEBOARD AS A LEARNING MEDIA IN PBL TUTORIAL DISCUSSION IN A MEDICAL SCHOOL AT INDONESIA - Prattama Santoso Utomo; Savitri Shitarukmi; Noviarina Kurniawati; Widyandana Widyandana (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2019)
Background: Learning media do have an important role in facilitating learning for medical students, especially in Problem Based Learning (PBL) curriculum. TV-LEDs, LCDs and whiteboards are currently popular to be used as the learning media for PBL tutorial discussions. TV-LEDs and LCDs are digital technologies which are considered more sophisticated when compared to whiteboards. Undergraduate medical students in Faculty of Medicine, Universitas Gadjah Mada (FM UGM), Yogyakarta-Indonesia attend PBL tutorials every week and use those learning media to facilitate their tutorial discussions. This study aimed to compare the effectiveness of TV-LEDs/LCDs and whiteboards as learning media in PBL tutorial discussion.Methods: A cross-sectional study using both qualitative and quantitative (mixed method) survey approaches. A total of 398 third and fourth year undergraduate medical students of FM UGM participated the survey. Data were collected using a questionnaire that incorporated close-ended questions using likert-scale (quantitative) and open-ended questions (qualitative). Quantitative data were analysed based in ARCS (Attention, Relevance, Confidence, Satisfaction) grouping method and qualitative data were analysed using deductive qualitative analysis.Results: The survey found based on ARCS groups that A = 3,68; R = 3,63; C = 3,69; S = 3,71. These results indicate that students are eager and enthusiastic in using the technology of TV-LEDs/LCDs as learning media. The qualitative responses describe the benefits and limitations of both TV-LEDs/LCDs and whiteboards as learning media in PBL tutorial. Students also provide some suggestions to optimise the benefits of both learning medias in facilitating learning in PBL tutorial.Conclusion: The use of TV-LEDs/LCDs as learning media in PBL tutorial received a positive response overall. TV-LEDs/LCDs are considered more effective and interactive rather than whiteboard. Students suggested that TV-LEDs/LCDs should be used side-by-side with whiteboard.Keywords: TV-LED/LCD, whiteboard, tutorial, learning media, effectiveness, medical student